ANALISIS IMPLEMENTASI PP NO. 12 TAHUN 2012 TENTANG INSENTIF PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KAWASAN DANAU DUSUN BESAR KOTA BENGKULU - Alimansyah, Alimansyah; Sariasih, Yenny; Yulianti, Yulianti (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2015)
This study aims to describe how the implementation of incentives as stipulated in Government Regulation No. 12 of 2012 concerning the protection of agricultural land incentives sustainable food in the Dusun Besar Lake area of the city of Bengkulu. This research is a descriptive study with a qualitative approach. Informants determination use purposive sampling. Data collection techniques consist of observation, interviews and discussions as well as documentation. Data analysis are conducted by inductively starting from data collection, data reduction, data presentation and data verification. Based on the results of a couple of aspects studied, namely communication, resources, disposition, and bureaucratic structures, further seen from the form of the provision of incentives in the form of : agricultural infrastructure development has not been run, the financing of research and development of improved varieties of seeds and no ease of access to information and existing technology (extension), the provision of production facilities, guarantee certificate issuance of land rights on agricultural land are not sustainable food and / or rewards for high achievers existing farmers, government programs. It was concluded that the implementation of the Regulation no 12tahun 2012 in incentives for farmers land owners in the Dusun Besar Lake area of the city of Bengkulu is not already running. While the constraints faced by the lack of regulations governing the area of land protection sustainable food. Therefore, intensive provision for sustainable food future land owners should be budgeted and city government programs through agencies or institutions concerned.